Thermodynamic constant of time passage - Dobija, MieczysÅ‚aw; Renkas, Jurij (International Journal of Physical Research, 2021)
The study of time has a long history and is still ongoing. The term formulated by Isaac Newton was coined in the 17th century, so naturally it could not relate to thermodynamics. Since the passage of time and aging are inalienable components of human experience, so Newton's concept of time was and is still alive. W.G. Leibniz and I. Kant mainly questioned the absoluteness of time. This paper introduces the definition of time and justifies the thesis that time is a thermodynamic process, flows uniformly, and the rate of passage of time is determined by a suitable natural constant.Â Â Â